Trans-Visibilities and Sexual Politics: Temporary Passages in Spanish Popular Cultures - Sabuco i Cantò, Assumpta (The Age of Human Rights Journal, 2022)
This article aims to review the models that historically have shaped technologies of gender through popular representations in Spanish culture. First, an anthropological view will be cast on the naturalised Catholic-Francoist models that exalted heterosexual dichotomies and reproductive marriage. This includes an analysis of how, although the criminalization of transsexuals aggravated their situation, resistance movements generated a wide range of cultural references and possibilities for inclusion. Second, the article will review the models associated with Spain’s transition to democracy and their evolution moving on to the beginning of the 21st century. Finally, it will draw an outline of the trans models produced during the past two decades and their popular expressions.